Upaya Meningkatkan Hasil Belajar Peserta Didik Dalam Mata Pelajaran Sejarah melalui Metode Pembelajaran Sort Card (Sortir Kartu) - Zurmaneli Susanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study is to describe and obtain information about efforts to improve student learning outcomes in History subjects through Sort Card Learning Methods in Class XII IPS 3 SMA N 1 Ranahan Batahan, West Pasaman Regency. This research is a classroom action research. Research procedures include planning, action, observation and reflection. Research data was collected using observation sheets and daily tests. Data were analyzed using percentages. Learning outcomes of students from cycle I to cycle II. The learning outcomes of students in the first cycle were 56.15 (sufficient), increasing to 84.04 (good) with an increase of 27.89%. Based on the results of the research and discussion that have been put forward, it can be concluded that the Sort Card Learning Method can improve the learning outcomes of students in the subjects of the History of the Indonesian Proclamation of Independence in N 1 High School Batahan. Keywords: Learning Outcomes, Sort Card Learning Method